Integrating Deep Learning Into School-Based Guidance and Counseling Services: Training Junior High School Counselors in the Socratic Method - Nandang Rusmana; Anne Hafina; Rina Nurhudi Ramdhani; Yusi Riksa Yustiana; Tati Kustiawati (IKIP Siliwangi, 2026)
The abstract should end with a comment about the importance of a brief outcome or conclusion. The integration of information and communication technology (ICT) in education often remains limited to knowledge transfer without adequately promoting critical thinking or emotional development. School counselors are expected to adopt holistic, student-centered approaches aligned with deep learning principles. This study aimed to enhance junior high school counselors' competencies in Garut Regency through Socratic method training as a strategy for implementing deep learning principles in guidance and counseling services. A qualitative participatory action research design was employed with 51 guidance and counseling teachers using the APPLE Facilitation Model (Assess, Plan, Prepare, Lead, Evaluate). Data were collected through reflective exercises, service plan development, practical implementation observations, and in-depth interviews, then analyzed using thematic analysis. Profound professional transformation emerged across four dimensions: identity shift from advice-givers to facilitators, enhanced student engagement, collaborative professional culture development, and increased comfort with uncertainty. Implementation outcomes showed 98% increased confidence in student-centered approaches, 91% motivation for facilitative methods, and 96% intention to implement Socratic questioning. The integration of deep learning principles through Socratic method training demonstrated significant promise for enhancing school-based guidance and counseling effectiveness. The APPLE model proved effective for systematic professional transformation in Indonesian educational contexts.